2014
DOI: 10.1016/j.ajhg.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Phevor Combines Multiple Biomedical Ontologies for Accurate Identification of Disease-Causing Alleles in Single Individuals and Small Nuclear Families

Abstract: Phevor integrates phenotype, gene function, and disease information with personal genomic data for improved power to identify disease-causing alleles. Phevor works by combining knowledge resident in multiple biomedical ontologies with the outputs of variant-prioritization tools. It does so by using an algorithm that propagates information across and between ontologies. This process enables Phevor to accurately reprioritize potentially damaging alleles identified by variant-prioritization tools in light of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
180
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(187 citation statements)
references
References 38 publications
3
180
0
Order By: Relevance
“…It is foreseeable that with phenotypic information, a heuristic variant-and disease-calling pipeline can be built and automated. 39 We also observed that compound heterozygous conditions are often not callable from NGS alone because current technologies cannot differentiate between cis or trans phasing. Of all 36 cases, identification of the disease-causing mutation was only missed in two cases (false negatives), with both being coding mutations in CYP21A2, which has a 98% homology to its pseudogene (CYP21A1) and frequently undergoes gene-conversion events.…”
Section: Discussionmentioning
confidence: 92%
“…It is foreseeable that with phenotypic information, a heuristic variant-and disease-calling pipeline can be built and automated. 39 We also observed that compound heterozygous conditions are often not callable from NGS alone because current technologies cannot differentiate between cis or trans phasing. Of all 36 cases, identification of the disease-causing mutation was only missed in two cases (false negatives), with both being coding mutations in CYP21A2, which has a 98% homology to its pseudogene (CYP21A1) and frequently undergoes gene-conversion events.…”
Section: Discussionmentioning
confidence: 92%
“…74 for a review) to elevate rankings of potential candidates in variant prioritization. These tools vary from ontology-based semantic similarity methods to more complex machine-learning techniques 7580 .…”
Section: Relevance To Diseasementioning
confidence: 99%
“…Phenotype analysis tools such as the Phenotype-Driven Variant Ontological Re-ranking tool (Phevor) 80 and Phenolyzer 78 can evaluate qualitative HPO-based phenotype descriptions such as ‘lethargy, seizures and hepatomegaly’ and use the broader structure of the HPO and its gene–symptom linkages in order to associate genes with proband phenotypes. They then combine this information with variant and gene prioritization results.…”
Section: Relevance To Diseasementioning
confidence: 99%
“…The analysis strategy to prioritize candidate variants scored them according to their effect on protein structure and phylogenetic conservation by using a seven-point scoring system (Pathogenic Variant or PAVAR 18 To improve the accuracy of the variant prioritization, we combined the previous results with other bioinformatics tools that include phenotype information such as Exomiser v.2, 21 and Variant Annotation Analysis and Search Tool (VAAST)+Phevor that prioritize the variants and the genes affected using a ranking system. 22,23 We used linkage information derived from the WES-common SNVs within each pedigree to reduce the list of candidate variants, according to the method described by Gazal et al 24 Validation by Sanger sequencing …”
Section: Bioinformatics Analysesmentioning
confidence: 99%